THE EFFECTS OF SOME FODDER ADDITIVES ON GROWTH PERFORMANCE OF SIBERIAN STURGEON (ACIPENSER BAERI) - C. Sverinciuc; M. I. Benţea; A. Șara (Agricultura, 2017)
The effects of fodder additives Actigen, Sel-Plex and Yea-Sacc-1026 on growth performance of juvenile Siberian sturgeon were investigated in this experiment. The experiment was carried on 108 sturgeon divided in four groups consisting of 27individuals each. The first group was fed with 0.08% Actigen added to daily feed, the second group had 0.03% Sel-Plex added to daily feed, the third group had 0.2% Yea-Sacc added to daily feed and the forth group (control) was fed regular feed with no additives. The experiment was carried out over a period of 18 weeks from the 1st of July to the 2nd of November 2016. Over the course of the experiment the following performance indices were monitored: specific growth rate, body mass, total biomass, food conversion ratio and survival rate. At the end of the experiment a 8.93% growth in body mass was observed in group 3 (Yea-Sacc 0.2%) compared with the control group. Total biomass recorded an 8.78% growth in group 3 (Yea-Sacc 0.2%) compared with the control group. The growth rate of group 3 (Yea-Sacc 0.2%) was 30.05% higher than the control group. The effects of the additives on survival rate were positive, no loss was recorded.